Identification of immunoreactive antigens in membrane proteins enriched fraction from Francisella tularensis LVS - Janovská, Sylva; Pávková, Ivona; Hubálek, Martin; Lenco, Juraj; Macela, Ales; Stulík, Jirí (Immunology letters, 2007)
Francisella tularensis is a Gram-negative, facultative intracellular bacterium causing disease in many mammalian species. The low infectious dose of F. tularensis and the ease of air-borne transmission are the main features responsible for the classification of this bacterium as a potential biological weapon. The live attenuated strain of F. tularensis live vaccine strain (LVS) is currently only effective vaccine against tularemia, however, this type of vaccine has not been approved for human use. In the presented study, sub-immunoproteome analysis was performed to search for new immunogenic proteins of Francisella tularensis LVS grown under different conditions. By this approach 35 immunoreactive antigens were identified, 19 of them showed to be novel immunogens. In conclusion, sub-immunoproteome analysis resulted in successful identification of novel immunoreactive proteins.
Keywords: Electrophoresis, Polyacrylamide Gel; Membrane Proteins; Antigens, Bacterial; 2D gelová elektroforéza; Humans; Tandem Mass Spectrometry; elektroforéza v polyakrylamidovém gelu; Immune Sera; antisérum; Francisella tularensis; antigeny bakteriální; lidé; výpočetní biologie; tandemová hmotnostní spektrometrie; Computational Biology; isoelektrická fokusace; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Isoelectric Focusing; Electrophoresis, Gel, Two-Dimensional; membránové proteiny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization